Most common bacterial agents in hospitalized patients with acute exacerbations of chronic obstructive pulmonary disease - Kolarov, Violeta; Zvezdin, Biljana; Djurić, Mrina; Hadnadjev, Mirjana; Hromiš, Sanja; Nikoletić, Katarina; Trivić, Bojana (Vojnosanitetski pregled, 2017)
Background/Aim. Infection is the major cause of acute exacerbation of chronic obstructive pulmonary disease (AE-COPD). The aim of the study was to establish the most common bacterial agents of AE-COPD in patients hospitalized in a tertiary medical care institution. Methods. This retrospective study included the patients hospitalized due to infective AE-COPD in the Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica in a 12-month period. We evaluated clinical data, spirometry, pathogen etiology in the patients with positive sputum findings and disease outcome. Results. The study included a total of 81 patients, 47 (58.02%) males and 34 (41.97%) females of the mean age of 65.7 years. The mean history of the disease was 14.5 years. The median forced expiratory volume in one second (FEV1) was 30.12%. The most common isolated pathogens was Pseudomonas aeruginosa (n = 36; 38.29%), followed by Haemophilus influenzae (n = 25; 26.59%) and Streptococcus pneumoniae (n = 16; 17.02%). Coinfections were present in 9 (9.57%) of the patients. The median FEV1 values of 28.67%, 37.23%, and 42.26% were registered in the patients with Pseudomonas aeruginosa, Haemophilus influenza, and Streptococcus pneumonia induced infection, respectively. The case fatality rate (CFR) was 6.2%. Of the deceased, 100% had Pseudomonas aeruginosa-induced infection. A statistically significant difference in FEV1 values was registered between the patients with and without Pseudomonas aeruginosa in their sputum finding (p = 0.016). Conclusion. The most common pathogens in patients with AE-COPD were Pseudomonas aeruginosa, Haemophilus influenzae, and Streptococcus pneumonia. The CFR was 6.2%. All (100%) deceased patients had the infection induced by Pseudomonas aeruginosa.